(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
Information and Communication Technology (ICT) policy is a code that clarifies the duties, responsibilities and rights of technology stakeholders and specifies acceptable and efficient ICT utilization. ICT policy is very fluid and rooted in a fast changing technology generating new issues and requirements. The study of ICT policy requires the organization to continuously adapt without having to make dramatic structural changes and with keeping long term focus. ICT policy life cycle encompasses four main processes which are: development, implementation, monitoring and evaluation. In many cases, the processes that form the life cycle of ICT policy usually stopped or failed at starting phase(s), including the case study in this research. Failures in ICT policy management may compromise ICT security, control and strategy in addition to incurring unnecessary expense. This study explored the challenges and issues in managing ICT policy in one of the Malaysian Public Institutions of Higher Education. An in-depth analysis and elaboration is performed using Viable System Model (VSM) and Hermeneutics method to diagnose and identify weaknesses, mismatches and viable requirements. The case documented here underlines the vast potential of the VSM in ICT policy analysis due to its flexibility and robustness that are a prerequisite in fast-changing environments. The evidence documented here represents the power of VSM through the application of its systemic functions and organizational structure that accommodates environmental dynamism, encourages sustainable development and provides sound theoretical platform. The paper demonstrates practical application of the VSM in diagnosing the organization that contribute towards the maturation of the field.